HUBUNGAN ANTARA KOMUNIKASI INTERPERSONAL SALES DENGAN PERILAKU KONSUMTIF - Malwa, Rosyidah Umpu (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2017)
Honda Union Palembang customers are generally upper middle classcustomers who tend to have buying behavior based on their wishes. This customer tendsto fulfill his needs a bit exaggerated (consumptive behavior). From this fulfillmentcustomers tend to buy a car because of interest in the latest unit variants, purchasedpackages that are considered cheap, or because bored with old cars. This should beunderstood by Honda sales, where they should be able to understand the marketsituation, so it can attract interest from customers. Sales must be able to understand andconvey Honda car information to customers well and effectively (interpersonalcommunication). So that the desired positive impact can occur ie the occurrence of saleand purchase transactions.The population in this study is a customer of Honda Union who made apurchase in March 2017 which amounted to 50 people aged 19-55 years of male andfemale sex.Data collection method or instrument used that is using likert scale method.Product Moment Pearson correlation analysis results. A correlation coefficient of 0.621was obtained with a significance value of 0.000 (p <0.05). The result of the closeness ofthe relationship is 38.56%. It shows that there is a significant influence betweeninterpersonal communication to consumptive behavior. While 61.44% is the influence ofother factors.